Evaluation of life extension by migrating the legacy TTS to be under HLA architecture. (2017) - Hui, Lin; Wang, Kuei Min
Numerous military existing simulation systems are faced with the phenomenon of aging, resulting in high maintenance costs and system instability issues. It would be expensive and risk in their retirement life extension and interoperability. The aim of this study was to analyse the aging tactical training simulation (TTS) system, to seek a way to transfer it under the HLA architecture to achieve, not only prolong life, but also gives interoperability. TTS assessment process including the restoration of the original structure and operation of the process, introduce the concept of HLA in the analysis of defects and ways to improve their TTS architecture such as replacing TTS_MANAGER module. We must complete upgrades as the main body of the TTS with HLA trunk: internal system of communication and APP modules. This study provides military traditional simulation systems solutions, and paved the way for the creation of synthetic battlefield environment, can benefit military training, planning, procurement and resource allocation scheme.